The impact of Infection Prevention and control (IPC) bundle implementationon IPC compliance during the Ebola virus outbreak in Mbandaka/Democratic Republic of the Congo: a before and after design. Issue 9 (5th September 2019) - Ousman, Kevin; Kabego, Landry; Talisuna, Ambrose; Diaz, Janet; Mbuyi, John; Houndjo, Bienvenu; Ngandu, Jean-Paul; Omba, Gaston; Aruna, Aaron; Mossoko, Mathias; Djingarey, Mamadou Harouna; Balde, Thierno; et al.
Abstract : Objectives: To assess the impact of refresher training of healthcare workers (HCWs) in infection prevention and control (IPC), ensuring consistent adequate supplies and availability of IPC kits and carrying out weekly monitoring of IPC performance in healthcare facilities (HCFs) Design: This was a before and after comparison study Settings: This study was conducted from June to July 2018 during an Ebola virus disease (EVD) outbreak in Equateur Province in the Democratic Republic of the Congo (DRC). Participants: 48 HCFs Interventions: HCWs capacity building in basic IPC, IPC kit donation and IPC mentoring. Primary outcome measures: IPC score Results: 48 HCFs were evaluated and 878 HCWs were trained, of whom 437 were women and 441 were men. The mean IPC score at baseline was modestly higher in hospitals (8%) compared with medical centres (4%) and health centres (4%), respectively. The mean IPC score at follow-up significantly increased to 50% in hospitals, 39% in medical centres and 36% in health centres (p value<0.001). The aggregate mean IPC score at baseline for all HCFs, combined was 4.41% and at follow-up it was 39.51% with a mean difference of 35.08% (p-value<0.001). Conclusions: Implementation of HCW capacity building in IPC, IPC kit donation to HCF and mentoring in IPC improved IPC compliance during the ninth EVD outbreak in the DRC.